The Development of Tempe Msme Cooperatives in Sidoarjo: A Strategy to Strengthen Competitiveness and Local Economic Independence - Ali Masyhuri, Mohammad (Universitas Muhammadiyah Surabaya, 2026)
The development of cooperatives as the main driver of tempeh Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo Regency, East Java, is an interesting model in the context of strengthening competitiveness and local economic independence. This study aims to analyze the strategies implemented by tempeh MSME cooperatives in Sidoarjo, using qualitative research methods with a case study approach at the Sidoarjo Branch of the Indonesian Tofu and Tempeh Producers Cooperative (KOPTI) and similar cooperatives. The results show that the strategy to strengthen competitiveness is carried out through supply chain consolidation, particularly the collective procurement of soybean raw materials (Dethier & Effenberger, 2012; Poulton et al., 2004). In terms of economic independence, cooperatives play a role as learning and inclusive financial institutions (Birchall & Ketilson, 2009) that facilitate increased managerial capacity, access to soft capital, and the formation of a broader marketing network. Synergy between cooperatives, local governments, and other supporting institutions has proven crucial in creating a sustainable business ecosystem (Mazzarol et al., 2018). Challenges faced include fluctuations in global soybean prices, competition with non-organic products, and the regeneration of business actors. It is concluded that the tempeh MSME cooperative in Sidoarjo has developed an effective integrative strategy to build collectivity-based competitiveness and promote local economic independence.